Phytosociological Analysis of Arnigad Micro-watershed in Mussoorie Hills of Garhwal Himalayas - , Sanjeev; Gera, Mohit; Sankhayan, Prem Lall (Indian Forester, 2006)
The present study was carried out in Arnigad micro-watershed covering an area of 13.43 km2 in Mussoorie hills of Garhwal Himalayan region. For the purpose of characterizing the species composition, vegetation structure and floristic diversity by land use categories, the entire watershed was delineated into four land uses, viz., forest, scrub forest, degraded and agricultural lands. In all, 64 species belonging to 63 genera and 56 families were found to be growing in the micro-watershed. The vegetation analysis showed that Quercus leucotrichophora, Acacia catechu, Eucalyptus spp. and Juglans regia were found to be dominant in forest, scrub forest, degraded and agriculture lands respectively for the tree stratum. Similarly Berberis aristata and Lantana camara were observed to be dominant in the shrub communities of forest and scrub forests respectively. Lantana camara was also found to be dominant in the shrub communities of degraded land. Results of the diversity index, concentration of dominance and equability on the three land uses, viz., forest, scrub forest and degraded land indicated that maximum diversity was observed in forest with respect to tree stratum followed by scrub forest and degraded lands, whereas in case of shrub and herb strata, scrub forest showed the maximum diversity. The maximum values on dominance were recorded for all the three strata of vegetation on degraded land indicating the presence of single or few species. The vegetation recorded on scrub forest was found to be more equitable compared to vegetation on forest and degraded land.